The ABC of NTFPs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
There is, today, no standard, agreed definition of non-timber forest products . This article has followed that given by the FAO: 'Non-wood forest products include all goods of biological origin, as well as services, derived from forest or any...